2019
DOI: 10.1088/1757-899x/536/1/012066
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Press Temperature on The Properties of Binderless Particleboard

Abstract: All experimental binderless particleboard were manufactured using coffee husk. In this case, we apply a method so called an oxidation method that uses 15% hydrogen peroxide (H2O2) and a Ferro-sulphate (FeSO4) 7.5% catalyst. The methods refer to JIS A 5908-2003 standard. In this paper, through the test, we evaluate some properties of the panel including density, modulus of rupture (MOR), modulus of elasticity (MOE), internal bond strength (IB), thickness swelling (TS) and water absorption (WA). The panel is mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…BBG170 showed significantly higher MOR, MOE, and IB values compared to BB170 (p < 0.05), indicating that smaller particles contribute favorably to mechanical contact between particles, as previously described for boards derived from other lignocellulosic materials [3,4,77]. This behavior is likely attributed to the larger surface area and effective bonding between particles, involving the chemical compounds of BSG (hemicellulose, lignin, among others), as discussed previously [3,18,75]. The properties observed in BBG170 indicate that reducing the particle size of BSG and increasing the pressing temperature up to 170 • C facilitate chemical bonding and mechanical interlocking and improve the structural integrity of the boards.…”
Section: Bsg-based Particleboardsupporting
confidence: 75%
See 2 more Smart Citations
“…BBG170 showed significantly higher MOR, MOE, and IB values compared to BB170 (p < 0.05), indicating that smaller particles contribute favorably to mechanical contact between particles, as previously described for boards derived from other lignocellulosic materials [3,4,77]. This behavior is likely attributed to the larger surface area and effective bonding between particles, involving the chemical compounds of BSG (hemicellulose, lignin, among others), as discussed previously [3,18,75]. The properties observed in BBG170 indicate that reducing the particle size of BSG and increasing the pressing temperature up to 170 • C facilitate chemical bonding and mechanical interlocking and improve the structural integrity of the boards.…”
Section: Bsg-based Particleboardsupporting
confidence: 75%
“…The chemical constituents of BSG possess the potential for chemical transformations in the presence of water during hot pressing. This includes processes such as hydrolysis, dehydration, and oxidation of hemicelluloses, which can subsequently polymerize and contribute to particle-to-particle adhesion [ 18 , 74 , 75 ]. Additionally, the combination of moisture and heat can induce the degradation, softening, and plasticization of lignin, increasing the occurrence of chemical interactions and crosslinking reactions that can favor self-adhesion [ 3 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several parameters influence the physical and mechanical properties of wood panels: chemical composition (Widyorini et al 2005;Lui et al 2018), particle size and geometry (Widyorini et al 2011;Kurokochi and Sato 2015a, b;Lui et al 2018;Ahmad et al 2019;Ferrandez-Villena et al 2020), pressing temperature (Okuda et al 2006a;Gao et al 2011;Hashim et al 2011;Boon et al 2013;Milawarni et al 2019;Song et al 2020), pressing time (Xu et al 2006;Gao et al 2011;Boon et al 2013;Ferrandez-Villena et al 2020), pressure (Boon et al 2013); water content (Widyorini et al 2005;Xu et al 2006), and pretreatment (Xu et al 2006;Takahashi et al 2010), etc. Trichomes and wart-like protuberances on the epidermis of herbaceous straw might inhibit the bonding between particles.…”
Section: Binderless Boardsmentioning
confidence: 99%
“…This trend has gained popularity due to the abundant availability of natural fibers, low density, high porosity, environmental sustainability, renewability, cost-effectiveness, and good insulation properties [3][4][5]. Many research efforts have been devoted to exploring the potential of natural fibers as the primary material for manufacturing particleboards, including but not limited to coffee skin [6][7][8][9], coconut coir fiber [11], and palm wood [12]. Additionally, previous studies have demonstrated the feasibility of using natural fibers as acoustic panel materials, such as hemp fiber [13], sisal, sugarcane, and banana [14].…”
Section: Introductionmentioning
confidence: 99%